The expression patterns of HSP70 and HSP90 genes of abalone (Haliotis squamata) using 2-phenoxyethanol as an anaesthetic during transportation - Yasa Ngurah S. (EDP Sciences, 2021)
The packaging of abalone (H. squamata) (39.65 ± 0.24 mm TL) for long-term transportation (>8 hours) requires the addition of substances that provide an anesthetic effect so that it could reduce stress and maintain survival rate post transportation without having to repack. The objective was to investigate the expression pattern of HSP70 and HSP90 genes of abalone during transport with the addition of 2-phenoxyethanol. Abalone was packed using a styrofoam box with dimensions (42.5 x 75.5 x 27.5 cm3), containing 2 pcs of 10L Polyethylene (PE) plastic bags. The plastic bag consisted of 2 pcs of 25cm, 4-inch Polyvinyl Chloride (PVC) pipe for abalone attached. Both ends line enclosed with screen net and tied with rubber bands. Abalone density was 50 heads/pipe. Transportation tests were carried out using a dry system and wet system with and without the addition of 2-phenoxyethanol (PK, KK). Data analysis was done by paired sample ttest and ANOVA with a 95% confidence interval. The results showed that the best abalone survival (85%) was obtained in wet transport + 2-phenoxyethanol (PB) (p <0.05) within 24 hours of transportation.